Management of Patent Ductus Arteriosus Endarteritis in Children - Canning, Jane; Occleshaw, Christopher; Iyengar, Ajay J.; Moosmann, Julia (The Thoracic and Cardiovascular Surgeon Reports, 2024)
The risk of patent ductus arteriosus infective endarteritis (PDA-IE) has significantly reduced since the introduction of antibiotics and surgical or interventional treatment strategies. However, diagnosis and adequate, timely management of PDA-IE remains challenging. We present the case of a 9-year-old girl with PDA-IE, illustrating our strategy to minimize complications in pediatric patients.
Keywords: patent ductus arteriosus; endarteritis; management